Copper-catalyzed synthesis of aryldiazo sulfones from arylhydrazines and sulfonyl chlorides under mild conditions. (27th August 2015) - Liu, Jin-Biao; Chen, Fu-Jiao; Liu, En; Li, Jin-Hui; Qiu, Guanyinsheng
Abstract : A simple and effective procedure for the preparation of aryldiazo sulfones by Cu-catalyzed sulfonylation/dehydrogenation is presented. Abstract : In this paper, aryldiazo sulfones are prepared from tandem sulfonylation/dehydrogenation reactions of arylhydrazines and sulfonyl chlorides. The transformations proceed well in the presence of catalytic CuSO4 ·5H2 O, leading to aryldiazo sulfones in good to excellent yields. It is believed that this protocol represents a safe and convenient model for the synthesis of these versatile aryldiazo sulfones under mild conditions.